Efektivitas Kinerja Klinik Pratama Badan Narkotika Nasional Provinsi Sumatera Utara dalam Merehabilitasi Rawat Jalan Pecandu Narkotika - Ela Dwi Tika; Syafruddin Ritonga; Rosmala Dewi (PERSPEKTIF, 2019)
Effectiveness is the degree to which a social system reaches its goal. While performance is a result of a whole during a certain period in carrying out his duties. The National Narcotics Agency Sumatra Province serves to assist the recovery of narcotics addicts or abuse by means of outpatient rehabilitation. As for the outpatient rehabilitation involves teams of doctors and nurses trained, Standard Operational Procedure that is conducted by a team of medical assesment service is to know the degree of severity and therapeutic rehabilitation plan for the client. This type of research is qualitative research methods focusing to clinical performance effectiveness pratama in outpatient rehabilitation for addicts of narcotic drugs. The nature of this research is descriptive. The location of the research carried out in the way of West V William Iskandar Market Numbers.1A Field Estate. The results showed that the performance of the employees Klinik Pratama is said to be quite effective due to obstacles. Factors that play a role in achieving clincial effectiveness pratama is the achievement of targets, adaptability, job satisfaction, and responsibility. The existing barriers in the form of skimpy budgets, a lack of medical personnel and the lack of infrastructure repair facility.